Assessment of the effect of glycation on the allergenicity of sesame proteins. (June 2023) - Jiang, Songsong; Wang, Tao; Chen, Kuan; Wang, Hengpeng; Meng, Xiangren
Graphical abstract: Highlights: Glycation with glucose, galactose, lactose and sucrose decreased the allergenicity of sesame proteins. Glycation with glucose, galactose, lactose and sucrose changed the secondary structure, the tertiary structure and the surface hydrophobicity of sesame proteins. Glycation with glucose was most effective in decreasing the allergenicity and changing the structure of sesame proteins. Abstract: Sesame allergy is a growing concern worldwide. In this study, sesame proteins was glycated with glucose, galactose, lactose and sucrose respectively, and the allergenicity of different glycated sesame proteins were assessed by a comprehensive strategy, including simulated gastrointestinal digestion in vitro, a BALB/c mice model, a rat basophilic leukemia (RBL)–2H3 cell degranulation model and a serological experiment. Firstly, simulated gastrointestinal digestion in vitro showed that glycated sesame proteins were more easily to digest than raw sesame. Subsequently, the allergenicity of sesame proteins was assessed in vivo by detecting the allergic indexes of mice, and results showed that the levels of total immunoglobulin E (IgE) and histamine were reduced in glycated sesame proteins treated mice. Meanwhile, the Th2 cytokines (IL-4, IL-5, and IL-13) were downregulated significantly, demonstrating that sesame allergy was relieved in glycated sesame treated mice. Thirdly, the RBL-2H3 cell degranulation model results showed that the release of β-hexosaminidase and histamine were decreased to different degrees in glycated sesame proteins treated groups. Notably, the monosaccharide glycated sesame proteins exhibited lower allergenicity both in vivo and in vitro . Furthermore, the study also analyzed the structure alteration of sesame proteins, and the results showed that the secondary structure of glycated sesame proteins were changed (the content of α-helix and β-sheet were reduced), and the tertiary structure of sesame proteins after glycation modification was also changed (microenvironment around aromatic amino acids was altered). Besides, the surface hydrophobicity of glycated sesame proteins was also reduced except sucrose glycated sesame proteins. In conclusion, this study demonstrated that glycation reduced the allergenicity of sesame proteins effectively, especially glycation with monosaccharides, and the allergenicity reduction might be related to structural changes. The results will provide a new reference for developing hypoallergenic sesame products.